Evaluación morfológica en la propagación vegetativa de gliricidia sepium (yuca de ratón), en cafetales de un año del Cantón Jipijapa - Acuña Acebo, Jesús Hipólito (2016)
This study evaluated the morphology of the vegetative propagation of G. sepium (mouse cassava) in coffee plantations of one year. These activities were carried out in the Cisne farm owned by Ing. Publio Vásquez, in the site of Naranjal de Jipijapa. Tropical dry and an altitude of 315 msnm The genetic material of G. sepium (mouse cassava) was collected from sites adjacent to the study area at coordinates 17m 553625, UTM 9853758. To calibrate the best length of G. sepium (mouse cassava) cuttings and to promote sowing, prior to the installation of the trial was considered a completely randomized design with 6 treatments. The research was experimental, the treatments had different lengths: T1 0.50 m, T2 1.00 m and T3 1.50 m with Biol and the same lengths for; T4, T5 and T6 without Biol, the depth for the establishment of all treatments was 0.30 m. We used the completely randomized design (DCA), supported with the Tukey comparison test. The treatments were evaluated at 8, 16 and 24 days after sowing and were: sprouting time, number of sprouts. Leaf length, number of leaves, fresh root weight, root length, number of roots were evaluated at the final 24 days of the trial and survival was verified that there were no dead cuttings during the investigation. It was verified that treatment 3 of 1.50 m of length with Biol, exceeded the other 5 treatments with and without Biol. The dose applied to treatments T1, T2, and T3 were: 1 liter of Biol + 19 liters of water, Applied at the base of the stake every 5 days after sowing. As a result it was observed that the treatment 3 stakes of 1.50 m with Biol had averages of: 4.5 shoots with length of 49.5 cm; Root length 56 cm; Number of roots 14; Number of sheets 14; And the weight of the fresh root 87.5 gr, surpassing in 60% to the other treatments.